ASSESSING THE INFLUENCE OF DESTINATION PERCEIVED ATTRIBUTES PERFORMANCE ON CHINESE TOURIST EMOTIONAL RESPONSES - Cao Jing Jing; Basri Rashid, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
All tourists hope to bring home a memorable experience after visiting a destination. This experience is essentially depending on the outcome of their encounters with the destination attributes. It is suggested that the outcome from the encounters may also lead to certain emotional responses. This paper empirically examines tourists’ visit experience of 486 Chinese tourists in Malaysia in terms of the influence of destination attributes performance on their positive and negative consumption emotions. A survey method was employed to collect data regarding tourist demographic information as well as destination attributes performance, and positive and negative emotional responses. The results of regression analyses show that the destination attributes performance significantly influence the positive and negative consumption emotions. This finding is beneficial to tourism and hospitality stakeholders in Malaysian particularly about perceived destination attribute performance by the Chinese tourists and relevant destination attributes that require attention for future improvement.